Portuguese Sign Language in museums: communication for the deaf community (Cadernos de Sociomuseologia, 2024)
According to legal guidelines, Portuguese museums must allow any citizen to independently and accessibly enjoy the museum space. However, the Portuguese deaf community still faces some obstacles in accessing these spaces. The number of museums and museum spaces accessible to the deaf community is less than one hundred, out of more than 400 museums across Portugal. The enjoyment and access to cultural heritage are gradually making progress towards full and high-quality accessibility. In order to ensure the quality of products and services provided to the deaf community, museums should adopt Best Practices. These guidelines will allow both parties to contribute to a more accessible society with full rightsKeywords: Portuguese deaf community; Museum accessibility; Language accessibility; Videoguide.